‘Tell me what he said! We’ll decide if it makes sense or not’: a case study of legal interpreting between English and Chinese in Britain - Leung, Ester S.M. (International Journal of Speech, Language and the Law, 2001)
The principle that, during police interviews, people who do not speakEnglish should have access to interpreters has long been established inlegal practice in the UK. However, very little is known about the extent towhich or how this principle is actually applied. The aim of this study wasto provide a close look at current legal interpreting practices in differenttypes of legal encounter in the UK. The broad questions guiding myanalysis were: what was actually going on in these events; what were thespecific problems associated with interpreting in legal settings; and whatwere the problems associated with interpreting between Cantonese andEnglish? What can the close study of interpreters as they interpret tell usabout the process of ‘interpretation’ in legal settings?An ethnographic approach was adopted to collect and analyse the data.I observed and audio-recorded four interpreting events which involvedChinese interpreters. In order to understand the process of interpretationand reflect the interpreter’s point of view, interviews with each interpreterinvolved were arranged immediately after the recorded data has been transcribed.The main finding emerging from this study is that the legal practitionersexerted most control over the interaction through their use of language.However, this control was sometimes undermined, knowingly or unwittingly,by both interpreters and clients. In addition, it was found that,while interpreting, the interpreters were trying to understand what wassaid, but that their understanding was shaped by their knowledge andexperience of the world. The interpreters in my study filtered informationwhich they deemed to be significant and relevant to the situation. Workingwith different languages and with different cultural traditions, the interpreterscould only interpret in ways which they thought were mostappropriate to the situation. For example in one interview, the policeneeded to find out whether the suspect had bought an MOT certificateknowing that purchase of the certificate was illegal. Since time of theaction was not marked in the suspect’s answers (because in Chinese theverb itself does not indicate time); the interpreter clarified with thesuspect, on her own initiative, whether he knew at the moment he boughtthe certificate that the purchase would constitute a crime. Interpreterswere making moment-by-moment decisions related to the unfolding of theinterpreting event rather than by reference to established procedures.Because of the complexity of the interactional processes and the powerasymmetries involved in events such as these, I argue for a more dialogicapproach to the study of legal interpreting, one which takes account of theparticipants’ understanding of particular legal interpreting events. I alsoargue for a more critical approach to the study of legal interpreting, onewhich takes full account of the wider institutional and discursive contextin which specific legal interpreters find themselves working.